A semiotic intertextual analysis of beauty influencers' communication strategies on youtube: uncovering meaning and influence by using Pierce's framework - Ariani Wardhani; Hanisa Hasan (International Journal of Visual and Performing Arts, 2023)
This research aims to conduct a semiotic intertextual analysis of beauty influencers on YouTube. Specifically, the study centers on two prominent beauty influencers, Andra Alodita, and Kornelia Meilinda, and their strategies for effectively promoting recommended lipstick products. The research was conducted employing a qualitative approach, utilizing Peirce's semiotic theory. The findings reveal that beauty influencers strategically employ visual elements to convey meaning and captivate viewers' attention. Both Andra Alodita and Kornelia Meilinda meticulously craft their content, considering factors such as color schemes, backgrounds, and object placement. They adopt distinct approaches to reviewing lipstick products tailored to diverse audiences and preferences. This multiplicity of perspectives enhances the complexity of semiotic elements within beauty influencer content and broadens the spectrum of meanings conveyed to viewers. Furthermore, the findings underscore the significance of semiotic intertextuality as a potent tool for beauty influencers to shape meaning, influence perceptions, and resonate with their extensive audience. These findings offer valuable insights for marketers, brands, and content creators seeking to leverage semiotics' potential in shaping beauty trends and consumer behavior.